Is Bangalore achieving herd immunity - Patil, Rajeev M.; Kethineni, Aparna; Mukhopadhyay, Arindam; Thangam, Saral (International Journal Of Community Medicine And Public Health, 2021)
The emergence of a novel coronavirus (SARS-CoV-2) in late 2019 has led to millions of infections and substantial morbidity and mortality across the world. COVID-19 caused by SARS-CoV-2 infection ranges from mild self-limiting disease to acute respiratory distress syndrome and death. India is presently reeling under the second wave of COVID-19 pandemic with more than 2,52,28,996 cases and 2,78,719 deaths as of 18 May, 2021 making it the country with highest reporting cases in the world. Till that date, Bangalore, the capital city of Karnataka alone reported a total of 22,42,065 COVID-19 positive cases overstretching Indian Health care system in this pandemic situation. Considering its high population densities and contact rates it poses a challenge for controlling COVID-19 which is transmitted directly from person to person. The question of herd immunity and how soon it would develop therefore appears to be highly relevant in the context of disease elimination programs.